2014
DOI: 10.1140/epjc/s10052-014-2818-2
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing of wormholes in the galactic halo region

Abstract: A recent study by Rahaman et al. has shown that the galactic halo possesses the necessary properties for supporting traversable wormholes, based on two observational results, the Navarro-Frenk-White density profile and the observed flat rotation curves of galaxies. Using a method for calculating the deflection angle pioneered by V. Bozza, it is shown that the deflection angle diverges at the throat of the wormhole. The resulting photon sphere has a radius of about 0.40 ly. Given the dark-matter background, de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(86 citation statements)
references
References 16 publications
2
84
0
Order By: Relevance
“…The present study provides a clue for possible existence of wormholes in most of the galaxies and provides a theoretical platform to seek observational evidence for wormholes by studying the scattering of scaler waves or from past data using ordinary light as well as one can use the method of gravitational lensing as a possible experiment (Kuhfittig 2014). Another suggestion have given by Torres et al (1998) that wormholes can be probed using light curves of gamma-ray bursts.…”
Section: Resultsmentioning
confidence: 78%
“…The present study provides a clue for possible existence of wormholes in most of the galaxies and provides a theoretical platform to seek observational evidence for wormholes by studying the scattering of scaler waves or from past data using ordinary light as well as one can use the method of gravitational lensing as a possible experiment (Kuhfittig 2014). Another suggestion have given by Torres et al (1998) that wormholes can be probed using light curves of gamma-ray bursts.…”
Section: Resultsmentioning
confidence: 78%
“…As a forthcoming work, we can check the viability of evolving WHs within the present formalism, as well as possible observational signatures these objects may imprint on the galactic halo, as they evolve [58][59][60]. With the purpose of further checking the reliability of the present theory, a cosmological model from the f (R, T ) = R + α R 2 + λT formalism shall also be reported soon in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…Basically, we consider the form of static spherically symmetric wormhole metric (5) 2 , where v φ indicates the rotational velocity. In [75][76][77][78], it is pointed out that m = 0.000001, which is a very small value (nearly zero) and hence leaving the red shift function as a constant (as we assumed in previous sections). A comparison of these metrics leads to the following relations:…”
Section: Gravitational Lensing Effect Of Wormhole For Simple F (R) = mentioning
confidence: 82%
“…For this purpose, we followed the procedure given in Refs. [75][76][77][78] and explored the convergence of deflection angle. It is observed that, for the obtained exact solution for f 1 (R) = R, the resulting integral diverges at wormhole throat and hence it is concluded that a photon sphere, with radius r 0 (closest path taken by the light ray) equal to radius of the throat, can be detected.…”
Section: Discussionmentioning
confidence: 99%